Designing [100]-oriented Mn0.988Ni0.012CoSi/epoxy composites with large and reversible magnetic-field-induced strain by curing under a rotating magnetic field - Zhishuo Zhang; Kai Zhang; Bin Chen; Shuang Pan; Yong Guo; Yuanyuan Gong; Feng Xu (Journal of Materials Research and Technology, 2023)
Nowadays, the development of magnetic energy-conversion devices stimulates the exploration of non-rare-earth materials and their polymer composites with large strain output under magnetic field. In this paper, we will provide a basic strategy to produce [100]-oriented Mn0.988Ni0.012CoSi/epoxy composites with large and reversible magnetic-field-induced strain at room temperature. The mixture of Mn0.988Ni0.012CoSi powders and epoxy is cured under a rotating magnetic field of 1 T, and [100] preferred orientation is obtained along the rotation axis. The formation of [100] preferred orientation is related to the ferromagnetic structure of Mn0.988Ni0.012CoSi and greatly enhances the magnetic-field-induced strain. For the composite with the weight fraction of epoxy = 15 wt. %, the absolute value of magnetic-field-induced strain under a magnetic field of 1 T reaches 1506 ppm, comparable to that of Terfenol-D single crystal and Terfenol-D-based magnetostrictive polymer composite. Since the magnetic-field-induced strain is originated from second-order metamagnetic transition, the observed magnetic-field-induced strain is reversible and independent of the direction of the magnetic field. Besides, these composites show good processing ability. Our results suggest that the [100]-oriented Mn0.988Ni0.012CoSi/epoxy composites have application potential in energy-conversion devices.